PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN KONSUMEN DALAM MENCUCI MOBIL PADA HIKAM CAR’S WASH PROCOT KABUPATEN TEGAL - Rizqi, M.; Sulistyani, Tri; Suryawan, Iwan (PERMANA, 2017)
The purpose of this study is 1). To find out the effect of the product on consumer decisions, 2). To find out the effect of prices on consumer decisions, 3). To find out the influence of place on Consumer Decisions, 4). To find out the effect of promotion on consumer decisions, 5). To determine the effect of the process on consumer decisions 6). To find out the influence of people on consumer decisions 7). To determine the effect of physical evidence on consumer decisions. The method used in this study is the survey research method. Data collection techniques used in this study are library study methods and questionnaires. While the data analysis techniques used are rank spearman correlation analysis and significance test of the correlation coefficient. There is a strong, positive and significant effect of the product on consumer decisions. There is a fairly strong, positive and significant influence on prices on consumer decisions. There is a fairly strong, positive and significant influence on the decisions of consumers. There is a fairly strong, positive and significant effect of promotion on consumer decisions. There is a fairly strong, positive and significant effect of the process on consumer decisions. There is a strong enough, positive and significant influence on the decisions of consumers. There is a strong, positive and significant influence on physical evidence of consumer decisions. Keywords: Products, Prices, Places, Promotions, Processes, People, Consumer Decisions.